Cu / spherical anatase crystal form TiO2 catalyst material, preparation method and application
By uniformly dispersing nanocopper on the spherical anatase crystal TiO2 support, Cu/spherical anatase crystal TiO2 catalyst material was prepared, which solved the problem of high temperature and poor stability of existing catalysts in the CO catalytic oxidation reaction, and achieved complete conversion of CO and good stability at lower temperatures.
Patent Information
- Application Number
- CN202510204894.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-15
AI Technical Summary
In the CO catalytic oxidation reaction, existing catalysts have problems such as high CO complete conversion temperature, poor stability, difficult material morphology, and complicated preparation methods.
The spherical TiO2 support was prepared by hydrothermal method using Cu/spherical anatase crystal-form TiO2 catalyst material, and the nanocopper was uniformly dispersed by deposition and precipitation method, and the loading was controlled between 4-6 wt%.
Complete conversion of CO at lower temperatures (130°C) and maintains the conversion rate stable during the 24-day activity test, with good stability and reaction activity.
Smart Images

Figure CN119819304A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst composite materials, and in particular to a Cu / spherical anatase crystal-type TiO2 catalyst material, a preparation method and an application thereof. Background Art
[0002] CO has a wide range of sources, and incomplete combustion of all carbon-containing substances can produce CO. It is estimated that the total annual emission in the world is 371 million tons, accounting for 30% of the five gases included in the air quality standard, ranking first in the emission of atmospheric pollutants. Excessive CO in the environment will hinder the normal combination of oxygen and hemoglobin, causing hypoxia of human tissues and cells, causing poisoning, suffocation and even death. In addition, due to its flammability and wide explosion limit (12.5% to 80%), there is also a risk of explosion in coal mines, fire scenes and other environments when the CO concentration is too high. At present, fire departments in various countries in the world have taken the removal of CO as the main performance standard of gas masks. Therefore, the elimination of CO in the environment has important practical significance.
[0003] As the most widely used catalyst in practice, supported precious metal catalysts are widely used in CO catalytic oxidation due to their mature industrial application background and good CO and O2 adsorption and activation performance. However, precious metal catalysts have disadvantages such as high cost and easy deactivation, which has prompted people to look for new catalysts that can replace precious metals.
[0004] Transition metal oxides are favored in the research of new CO oxidation catalysts because of their high reserves, low prices, good valence change ability and redox ability, and high activity in many reactions. Copper is a competitive alternative to traditional precious metal catalysts because of its multiple valence states, low price, and abundant reserves. Titanium oxide (TiO2) has attracted much attention due to its excellent stability, low cost, and strong interaction with Cu. The micromorphology of non-precious metal catalysts plays an important role in the CO catalytic oxidation reaction process, and catalytic materials with certain sizes and morphologies have received widespread attention. However, the existing catalytic system still has practical problems such as high CO complete conversion temperature, poor stability, difficult to control material morphology, and cumbersome preparation methods.
[0005] At the same time, as a colorless, odorless, non-irritating toxic gas, it is also very important to monitor the concentration of CO in a specific environment. Therefore, gas sensors are widely used in many fields. This also makes researchers have higher and higher requirements for the sensitivity and stability of gas sensors. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0007] To this end, the first object of the present invention is to provide a Cu / spherical anatase crystal TiO2 catalyst material, the catalyst material comprising a TiO2 carrier and nano-copper uniformly dispersed and loaded on the TiO2 carrier; the TiO2 carrier is a spherical anatase crystal TiO 2, The loading amount of the nano copper on the carrier is 4-6wt%. The catalyst material carrier of the present invention is a spherical material with a specific morphology, has a high specific surface area and a rich pore structure, and can increase the contact area between the reactant and the catalyst and the transmission rate of the reactant species. At the same time, the spherical anatase crystal TiO2 carrier with a specific morphology strongly interacts with the Cu metal active component, promotes the adsorption and activation of the reactant molecules CO and O2, and disperses and stabilizes the metal Cu, while promoting its high dispersion and improving the catalytic activity, it can prevent the agglomeration and growth of the metal component. The product has both good reaction activity and stability, and has good practical application prospects.
[0008] In addition, the catalyst material according to the above embodiment of the present invention may also have the following additional technical features:
[0009] According to an embodiment of the present invention, the particle size of the nano copper is 1.73-1.79 nm.
[0010] The embodiment of the present invention also provides a method for preparing a Cu / spherical anatase crystal TiO2 catalyst material, and the specific preparation process is as follows: taking an organic titanium precursor and anhydrous ethanol, dropwise adding them to an acidic aqueous solution under stirring conditions to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction; roasting the hydrothermal reaction product to obtain a spherical titanium dioxide carrier with a specific morphology; taking the titanium dioxide carrier and dispersing it in deionized water to form a suspension, adding a Cu precursor solution thereto for deposition and precipitation, and roasting the obtained precipitate to obtain a Cu / spherical anatase crystal TiO2 catalyst. The catalyst material preparation method of this embodiment has low cost, simple preparation method, mild conditions, controllable process, and strong repeatability.
[0011] The method according to the above embodiment of the present invention may also have the following additional technical features:
[0012] According to an embodiment of the present invention, the hydrothermal reaction product is calcined at a temperature of 430-460° C. for 3-4 hours; the precipitate is calcined at a temperature of 330-360° C. for 3-4 hours.
[0013] According to an embodiment of the present invention, the ratio of the organic titanium precursor to anhydrous ethanol is 1:2, the organic titanium precursor is butyl titanate, and the acidic aqueous solution is 1-3 mol / L sulfuric acid or hydrochloric acid solution.
[0014] According to an embodiment of the present invention, the hydrothermal reaction temperature is 150-200° C., and the hydrothermal reaction time is 4-6 hours.
[0015] According to an embodiment of the present invention, the metal mass concentration in the Cu precursor solution is 1.5-2 mg / mL.
[0016] According to an embodiment of the present invention, the specific process of adding the Cu precursor solution to the suspension for deposition precipitation is: adding the Cu precursor solution to the suspension, then adjusting the pH with a Na2CO3 solution, then stirring the reaction, standing for aging, filtering, washing, and drying.
[0017] According to an embodiment of the present invention, the concentration of the Na2CO3 solution is 0.2 mol / L, the pH value is 9-10, the stirring reaction temperature is 80°C, the reaction time is 3 hours, and the static aging time is 1 hour.
[0018] An embodiment of the present invention also provides an application of a Cu / spherical anatase crystal TiO2 catalyst material, wherein the catalyst is applied to a CO catalytic oxidation reaction, wherein the catalyst completely converts CO at 130°C and maintains a stable conversion rate during a 24-day activity test, wherein the complete conversion of CO can be achieved at a relatively low temperature and has good stability.
[0019] The embodiment of the present invention also provides a method for gas-sensitive monitoring of trace CO gas using a Cu / spherical anatase crystal TiO2 catalyst material. At an operating voltage of 3.5V, the response value of the catalyst material to 1000ppm CO is 19.4mV, which has excellent gas-sensitive monitoring sensitivity for flammable, explosive, toxic and harmful gases. The catalyst material of the present invention can be used in a CO gas-sensitive sensor, and has CO elimination and detection functions.
[0020] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0022] Figure 1 The present invention is a flow chart of the method for preparing the Cu / spherical anatase crystal TiO2 catalyst material.
[0023] Figure 2 This is a graph showing the CO conversion test results of the catalysts prepared in Examples 1, 2 and 3 of the present invention.
[0024] Figure 3This is a graph showing the CO conversion rate test results of the catalysts prepared in Examples 1, 4 and 5 of the present invention.
[0025] Figure 4 This is a graph showing the CO conversion rate test results of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 of the present invention.
[0026] Figure 5 The XRD diagrams of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 of the present invention are shown.
[0027] Figure 6 These are electron microscope (TEM) images of the catalysts prepared in Example 1 (Figure a) of the present invention, Comparative Example 1 (Figure b) and Comparative Example 2 (Figure c).
[0028] Figure 7 It is a statistical diagram of Cu particle size of Example 1 of the present invention and Comparative Examples 1 and 2.
[0029] Figure 8 The stability comparison chart of the catalysts prepared in Example 1 of the present invention and Comparative Example 2 is shown.
[0030] Fig. 9 Graph showing the CO oxidation activity of the catalysts prepared in Example 1 of the present invention and Comparative Example 3.
[0031] Fig.10 This is a diagram of the CO oxidation activity of the catalysts prepared in Example 1 of the present invention and Comparative Example 4.
[0032] Fig.11 The response change curves of different materials prepared in Example 1 of the present invention and Comparative Examples 1 and 2 to CO gas at different working voltages are shown.
[0033] Fig.12 The sensing stability of different materials prepared in Example 1 of the present invention and Comparative Examples 1 and 2 to CO gas.
[0034] Fig.13 The XPS graphs of the catalysts prepared in Example 1 of the present invention and Comparative Examples 1 and 2 are shown.
[0035] Fig.14 H2-TPR diagram of the catalysts prepared in Example 1 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0037] According to one aspect of the present invention, the present invention provides a Cu / spherical anatase crystal TiO2 catalyst material, the catalyst material of the present invention comprises a TiO2 carrier and nano copper uniformly dispersed and loaded on the TiO2 carrier, the TiO2 carrier is a spherical anatase crystal TiO2 with a specific morphology, has a high specific surface area and a rich pore structure, can increase the contact area between the reactant and the catalyst and the transmission rate of the reactant species. At the same time, the spherical anatase crystal TiO2 carrier with a specific morphology strongly interacts with the Cu metal active component, promotes the adsorption and activation of the reactant molecules CO and O2, and disperses and stabilizes the metal Cu, while promoting its high dispersion and improving the catalytic activity, it can prevent the agglomeration and growth of the metal component, and the product has good reaction activity and stability. In addition, the loading amount of nano copper on the carrier affects the catalytic effect of the catalyst, the loading amount of nano copper on the carrier implemented by the present invention is 4-6wt%, by controlling the loading amount of nano copper to 4-6wt%, the catalyst active component can be fully utilized, it is not easy to form large agglomeration accumulation, and the effective copper active component is uniformly dispersed, and the catalytic performance is improved. The catalyst material of the present invention has both good reaction activity and stability and has good practical application prospects.
[0038] In some embodiments, the particle size of nano copper is 1.73-1.79 nm. The present invention can improve the dispersion performance by uniformly dispersing the catalyst active component Cu in nanometer form on the titanium oxide carrier, making the dispersion higher and more uniform, thereby improving the catalytic activity of the catalyst material.
[0039] The present invention also provides a method for preparing a Cu / spherical anatase crystal TiO2 catalyst material, referring to Figure 1 According to an embodiment of the present invention, the method includes:
[0040] Preparation of support by hydrothermal reaction of S100 organic titanium precursor
[0041] According to an embodiment of the present invention, an organic titanium precursor and anhydrous ethanol are added dropwise into an acidic aqueous solution under stirring conditions to obtain a mixed solution, and then the mixed solution is subjected to a hydrothermal reaction.
[0042] It is understandable that the carrier of the present invention is prepared by a hydrothermal reaction method, that is, a certain amount of an organic titanium precursor and anhydrous ethanol mixed solution are added dropwise to an acidic aqueous solution under stirring, and then the mixed solution is transferred to a hydrothermal reactor for hydrothermal reaction at a certain temperature. The present invention prepares the carrier by hydrothermal reaction, and not only the preparation method is simple, but also the morphology of the prepared carrier can be controlled so that the prepared carrier is spherical, and the morphology of the spherical carrier can improve the dispersibility of the active component on the carrier, and can prevent the agglomeration of the active component. In addition, there is a strong metal carrier effect, which can produce more oxygen vacancies on the catalyst surface, promote the adsorption activation of the reactant molecules CO and O2, and improve the reaction performance.
[0043] In some embodiments, the ratio of the organic titanium precursor to anhydrous ethanol is 1:2, the organic titanium precursor can be butyl titanate or other organic titanium, and the acidic aqueous solution is 1-3 mol / L sulfuric acid or hydrochloric acid solution.
[0044] In some embodiments, the hydrothermal reaction temperature is 150-200° C., and the hydrothermal reaction time is 4-6 hours. Under this hydrothermal condition, a spherical titanium dioxide product can be obtained, and the product size can be controlled. The hydrothermal reaction temperature affects the precursor hydrolysis rate, and then affects the crystal nucleation rate and growth rate, while the reaction time affects the product particle size and specific surface area.
[0045] S200 hydrothermal reaction product is calcined
[0046] According to an embodiment of the present invention, the product obtained by the hydrothermal reaction of the present invention is washed, dried and calcined to obtain a spherical titanium dioxide carrier with a specific morphology.
[0047] In some embodiments, the conditions for drying the hydrothermal reaction product are preferably 60-80°C, and drying in an oven for 10-12 hours; the conditions for calcination are preferably 430-460°C, and calcination in a muffle furnace for 3-4 hours. This is because the hydrothermal reaction product can obtain a suitable specific surface area and pore structure after drying and calcining at a suitable temperature and time, which is conducive to the diffusion of reactants and products, reduces the occupancy of active components, and improves catalytic performance.
[0048] S300 Cu precursor solution is deposited on the support
[0049] According to an embodiment of the present invention, the titanium dioxide carrier is dispersed in deionized water to form a suspension, a Cu precursor solution is added thereto for deposition and precipitation, and the obtained precipitate is calcined to obtain a Cu / spherical anatase crystal TiO2 catalyst.
[0050] It is understood that the catalyst of the present invention is prepared by a deposition precipitation method, taking a Cu precursor solution, adding 50 mL of deionized water to stir and dilute, and adding dropwise to a carrier suspension under strong stirring, adjusting the pH with a Na2CO3 solution, stirring the reaction, standing for aging, filtering, washing, drying, and roasting to obtain the target catalyst. The catalyst of the present invention is a precursor solution loaded on a carrier by a deposition precipitation method, the preparation method is simple, the conditions are mild, the process is controllable, the repeatability is strong, and the precursor active components can be evenly distributed on the carrier surface, thereby improving the catalytic effect.
[0051] In some embodiments, the metal mass concentration in the Cu precursor solution is 1.5-2 mg / mL. During the catalyst preparation process, the Cu precursor solution with this concentration can make Cu more evenly dispersed when mixed with the carrier, which is beneficial to reduce the aggregation of Cu components, make the Cu active components evenly distributed, and improve the catalytic effect.
[0052] In some embodiments, the concentration of Na2CO3 solution is 0.2 mol / L, the pH value is 9-10, the stirring reaction temperature is 80°C, the time is 3 hours, the static aging time is 1 hour, and the drying condition is preferably dried in an oven at 70-80°C for 10-12 hours. These conditions can control the sedimentation rate of Cu, make it more evenly loaded on the carrier, and improve the catalytic performance.
[0053] In some embodiments, the precipitate is preferably calcined at 330-360° C. in a muffle furnace for 3-4 hours. The catalyst calcination conditions of the present invention can make the active component Cu have suitable crystallinity and size, thereby improving the catalytic performance. The catalyst calcination temperature affects the crystal size and crystallinity of the active component Cu. If the temperature is too low, the crystallinity is insufficient, and if the temperature is too high, the size becomes larger. Therefore, a suitable catalyst calcination temperature is conducive to improving the catalytic performance.
[0054] An embodiment of the present invention also provides an application of a Cu / spherical anatase crystal TiO2 catalyst material, wherein the catalyst is applied to a CO catalytic oxidation reaction, wherein the catalyst completely converts CO at 130°C and maintains a stable conversion rate during a 24-day activity test, wherein the complete conversion of CO can be achieved at a relatively low temperature and has good stability.
[0055] The embodiment of the present invention also provides a method for gas-sensitive monitoring of trace CO gas using a Cu / spherical anatase crystal TiO2 catalyst material. At an operating voltage of 3.5V, the response value of the catalyst material to 1000ppm CO is 19.4mV, which has excellent gas-sensitive monitoring sensitivity for flammable, explosive, toxic and harmful gases. The catalyst material of the present invention can be used in a CO gas-sensitive sensor, and has CO elimination and detection functions.
[0056] The present invention is described below with reference to specific examples and comparative examples. It should be noted that these examples are merely illustrative and are not to be construed as limiting the present invention.
[0057] Embodiment 1:
[0058] 5mL of a mixed solution of butyl titanate and 10mL of anhydrous ethanol was added dropwise to a 2mol / L sulfuric acid solution under stirring. The mixed solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 180°C for 5h. The obtained product was washed by centrifugation with water and ethanol, and then dried in an oven at 70°C for 12h. After being taken out, it was ground and calcined in a muffle furnace at 450°C for 3h to obtain spherical titanium dioxide with a specific morphology, which was recorded as TiO2-S.
[0059] Disperse 1.00g TiO2-S carrier in 100mL deionized water to form a suspension; take 25mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / LNa2CO3 solution, stir and react for 3h in a 80℃ water bath, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 350℃ for 4h to obtain 5wt% Cu / TiO2-S material.
[0060] Embodiment 2:
[0061] Compared with Example 1, the calcination temperature in this example is changed.
[0062] 5 mL of a mixed solution of butyl titanate and 10 mL of anhydrous ethanol was added dropwise to a 2 mol / L sulfuric acid solution under stirring. The mixed solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 180°C for 5 hours. The obtained product was washed by centrifugation with water and ethanol, and then dried in an oven at 70°C for 12 hours. After being taken out, it was ground and calcined in a muffle furnace at 400°C for 3 hours to obtain spherical titanium dioxide with a specific morphology, which was recorded as TiO2-SL.
[0063] Disperse 1.00g TiO2-SL carrier in 100mL deionized water to form a suspension; take 25mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / LNa2CO3 solution, stir and react for 3h in a 80℃ water bath, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 300℃ for 4h to obtain 5wt% Cu / TiO2-SL material.
[0064] Embodiment 3:
[0065] Compared with Example 1, the calcination temperature in this example is changed.
[0066] 5 mL of a mixed solution of butyl titanate and 10 mL of anhydrous ethanol was added dropwise to a 2 mol / L sulfuric acid solution under stirring. The mixed solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 180°C for 5 hours. The obtained product was washed by centrifugation with water and ethanol, and then dried in an oven at 70°C for 12 hours. After being taken out, it was ground and calcined in a muffle furnace at 500°C for 3 hours to obtain spherical titanium dioxide with a specific morphology, which was recorded as TiO2-SH.
[0067] Disperse 1.00g TiO2-SH carrier in 100mL deionized water to form a suspension; take 25mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / LNa2CO3 solution, stir and react for 3h in a 80℃ water bath, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 400℃ for 4h to obtain 5wt% Cu / TiO2-SH material.
[0068] Embodiment 4:
[0069] Compared with Example 1, this example changes the load amount.
[0070] 5mL of a mixed solution of butyl titanate and 10mL of anhydrous ethanol was added dropwise to a 2mol / L sulfuric acid solution under stirring. The mixed solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 180°C for 5h. The obtained product was washed by centrifugation with water and ethanol, and then dried in an oven at 70°C for 12h. After being taken out, it was ground and calcined in a muffle furnace at 450°C for 3h to obtain spherical titanium dioxide with a specific morphology, which was recorded as TiO2-S.
[0071] Disperse 1.00g TiO2-S carrier in 100mL deionized water to form a suspension; take 10mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / LNa2CO3 solution, stir and react for 3h in a 80℃ water bath, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 350℃ for 4h to obtain 2wt% Cu / TiO2-S material.
[0072] Embodiment 5:
[0073] Compared with Example 1, the loading amount was changed.
[0074] 5mL of a mixed solution of butyl titanate and 10mL of anhydrous ethanol was added dropwise to a 2mol / L sulfuric acid solution under stirring. The mixed solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 180°C for 5h. The obtained product was washed by centrifugation with water and ethanol, and then dried in an oven at 70°C for 12h. After being taken out, it was ground and calcined in a muffle furnace at 450°C for 3h to obtain spherical titanium dioxide with a specific morphology, which was recorded as TiO2-S.
[0075] Disperse 1.00g TiO2-S carrier in 100mL deionized water to form a suspension; take 50mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / L Na2CO3 solution, stir and react in a 80℃ water bath for 3h, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 350℃ for 4h to obtain 10wt% Cu / TiO2-S material.
[0076] Comparative Example 1:
[0077] Preparation of rod-shaped Cu / TiO2-R
[0078] First, dissolve 2mL of concentrated hydrochloric acid in 50mL of distilled water and stir evenly. Place the prepared dilute hydrochloric acid solution in an ice-water bath and add 6.6mL of TiCl4 solution dropwise while stirring to obtain a clear solution a. Dilute 20mL of ammonia water with 80mL of distilled water, and then drop the solution in a dropwise into the dilute ammonia water while stirring to obtain a white suspension. After the addition is complete, adjust the pH of the solution to 9 and stir the mixed solution at room temperature for 2h. Wash the mixed solution with centrifugal water to obtain a white Ti(OH)4 precursor. Disperse the Ti(OH)4 precursor in a mixed solution of 0.5g(NH4)2SO4, 15mL of distilled water, and 15mL of isopropanol, stir and ultrasonically disperse for 10min to obtain a uniform suspension. Then transfer the suspension to a reactor and hydrothermally react at 180℃ for 12h. After the reaction is completed, centrifuge and wash with distilled water and ethanol respectively. It was then dried at 70°C overnight and calcined at 450°C for 3h to obtain rod-shaped titanium dioxide, which was designated as TiO2-R.
[0079] Disperse 1.00g TiO2-R carrier in 100mL deionized water to form a suspension; take 25mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / L Na2CO3 solution, stir and react in a 80℃ water bath for 3h, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 350℃ for 4h to obtain 5wt% Cu / TiO2-R material.
[0080] Comparative Example 2:
[0081] Preparation of octahedral Cu / TiO2-O
[0082] First, dissolve 2mL of concentrated hydrochloric acid in 50mL of distilled water and stir evenly. Place the prepared dilute hydrochloric acid solution in an ice-water bath and add 6.6mL of TiCl4 solution dropwise while stirring to obtain a clear solution a. Dilute 20mL of ammonia water with 80mL of distilled water, and then drip the solution in a dropwise into the dilute ammonia water while stirring to obtain a white suspension. After the addition is complete, adjust the pH of the solution to 9. Then stir the mixed solution at room temperature for 2h. Wash the mixed solution with centrifugal water to obtain a white Ti(OH)4 precursor. Disperse the Ti(OH)4 precursor in a mixed solution of 2g NH4Cl, 15mL of distilled water, and 15mL of isopropanol, stir and ultrasonically disperse for 10min to obtain a uniform suspension. Then transfer the suspension to a reactor and hydrothermally react at 180℃ for 12h. After the reaction is completed, centrifuge and wash with distilled water and ethanol respectively. It was then dried at 70°C overnight and calcined at 450°C for 3h to obtain rod-shaped titanium dioxide, which was recorded as TiO2-O.
[0083] Disperse 1.00g TiO2-O carrier in 100mL deionized water to form a suspension; take 25mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / L Na2CO3 solution, stir and react for 3h in a 80℃ water bath, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 350℃ for 4h to obtain 5wt% Cu / TiO2-O material.
[0084] Comparative Example 3:
[0085] Preparation of spherical Cu / TiO2 by different methods
[0086] Take 2.25g of titanium sulfate and dissolve it in 188mL of deionized water, stir at room temperature for 30min, then add 2.25g of urea, stir ultrasonically for 20min, transfer to a hydrothermal reactor and react at 180℃ for 1h. After the reaction, wash with water and ethanol by centrifugation, and then put it in an oven at 80℃ for 12h. After drying, take it out and grind it, and calcine it at 450℃ in a muffle furnace for 3h to obtain spherical TiO2-S2.
[0087] Disperse 1.00g TiO2-S2 carrier in 100mL deionized water to form a suspension; take 25mL 2mg / mL Cu(NO3)2 solution, add it to 50mL deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / L Na2CO3 solution, stir and react for 3h in a 80℃ water bath, and let it stand for aging for 1h. After the reaction is completed, filter with 2L 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 350℃ for 4h to obtain 5wt% Cu / TiO2-S2 material.
[0088] Comparative Example 4:
[0089] Preparation of Cu / TiO2 from Commercial TiO2
[0090] Disperse 1.00g of commercial anatase TiO2 carrier in 100mL of deionized water to form a suspension; take 25mL of 2 mg / mL Cu(NO3)2 solution, add it to 50mL of deionized water, stir and dilute, and add it dropwise to the carrier suspension under strong stirring, adjust the pH to 9.5 with 0.2mol / L Na2CO3 solution, stir and react for 3h in a 80℃ water bath, and let it stand for aging for 1h. After the reaction is completed, filter with 2L of 80℃ deionized water, and then put it in an oven at 80℃ to dry. After drying, take it out and grind it, and then put it in a muffle furnace at 350℃ for 4h to obtain 5wt% Cu / TiO2-anatase material.
[0091] The materials prepared in the above Examples 1-5 and Comparative Examples 1-4 were tested for performance:
[0092] 1. Catalytic performance test steps:
[0093] The catalyst was tested for CO oxidation activity using a fixed bed microreactor evaluation device. The catalyst dosage was 100 mg, the reaction gas volume composition was 1 vol.% CO + 5 vol.% O2 + Ar, the total gas flow rate was 30 mL / min (STP), the mass space velocity was 1.8×104 mL gcat-1h-1, and the catalyst was reduced at 300°C for 1 h in a 10 vol.% H2 / He atmosphere before the test, and then purged with argon to the test start temperature. The test temperature range was 70-200°C, and samples were taken after keeping the temperature constant for 20 minutes at each temperature point to be tested. The gas composition at the reactor outlet was detected by chromatography, and the conversion rate was calculated.
[0094] The CO conversion rate is calculated as follows:
[0095] CO Conversion(%)={([CO]in–[CO]out) / [CO]in}×100%
[0096] Where: [CO]in, [CO]out are the CO chromatographic peak areas of the feed and reactor outlet respectively.
[0097] 2. Gas sensing performance test steps:
[0098] Assemble the sensor: Take an appropriate amount of sample and place it in an agate grinder, grind for 5 minutes. Use a pipette to drip a little deionized water and mix it into a uniform solution, then use a fine brush to evenly apply it on the surface of the ceramic tube. Wait for its adhesion to stabilize. Perform welding, set the voltage to about 220V on a small precision energy storage spot welder, and stably weld the metal wires at both ends of the ceramic tube to the metal strip of the plastic test element to ensure that it will not fall off. Next, use a heating wire to pass through the center of the ceramic tube and also weld it to the metal strip of the plastic test element to complete the assembly of the component.
[0099] The gas-sensitive performance test of the sensing material is carried out using the WS-03 manual catalytic element test system produced by Henan Weisheng Electronics Co., Ltd. The specific operating steps of the test are as follows: First, before conducting the gas-sensitive test, the balance value in the air needs to be zeroed to ensure the accuracy of the test. Then connect the four leads to the corresponding four pins on the sensing element. After stabilization in the air, a reaction value will appear on the instrument, recorded as Va. Then use a syringe to draw a certain amount of CO gas and inject it into the gas cylinder. After stabilization, another reaction value will appear, recorded as Vg. Therefore, the response value of the sensor to 1000ppm CO gas can be obtained. The response formula is:
[0100] ΔV=|Vg-Va|
[0101] Where Vg is the response value of the sensor in the gas to be detected, and Va is the response value of the sensor in air. By adjusting the heating voltage on the test system, the response to 1000ppm CO gas at different voltages can be tested.
[0102] 3. Test results
[0103] (1)Reference Figure 2 The catalysts prepared in Examples 1, 2 and 3 of the present invention were used to catalytically convert CO. The testing method was carried out according to the catalytic performance testing steps of the present invention to test the conversion rate of CO by the catalysts.
[0104] Depend on Figure 2 It can be seen that when the carrier calcination temperature is about 450°C and the precipitate catalyst calcination temperature is about 350°C, the catalyst exhibits the best catalytic activity, and can achieve complete conversion of CO at 130°C; when the carrier calcination temperature is 400°C and the catalyst calcination temperature is about 300°C, complete conversion of CO can be achieved at 140°C; and when the carrier calcination temperature is 500°C and the catalyst calcination temperature is about 400°C, complete conversion of CO can be achieved at about 150°C. It can be seen that the low-temperature CO oxidation activity of the catalyst prepared by the present invention is closely related to the calcination temperature in the preparation process. This is because the carrier can obtain a suitable specific surface area and pore structure after being calcined at a suitable temperature, which is conducive to the diffusion of reactants and products, reduces the occupancy of active components, and improves the catalytic performance. The catalyst calcination temperature affects the crystal size and crystallinity of the active component Cu. If the temperature is too low, the crystallinity is insufficient, and if the temperature is too high, the size becomes larger, so a suitable catalyst calcination temperature is conducive to improving the catalytic performance.
[0105] (2)Reference Figure 3 The catalysts prepared in Examples 1, 4 and 5 of the present invention were used to catalytically convert CO. The testing method was carried out according to the catalytic performance testing steps of the present invention to test the conversion rate of CO by the catalysts.
[0106] Depend on Figure 3 It can be seen that when the Cu loading is 5wt%, i.e., 4-6wt%, the catalyst exhibits the best catalytic activity, and can achieve complete CO conversion at 130°C. This is because when the copper loading is too much, it is easy to accumulate and agglomerate to form large crystals, which reduces the effective active components and poors the catalytic performance; when the loading is too little, the number of active components decreases and the catalytic performance still deteriorates. In the present invention, when the Cu loading is controlled at 4-6wt%, the catalyst exhibits the best catalytic activity.
[0107] (3)Reference Figure 4The catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention were used to catalytically convert CO. The testing method was carried out according to the above-mentioned catalytic performance testing steps of the present invention to test the conversion rate of CO by the catalyst.
[0108] Depend on Figure 4 It can be seen that when rod-shaped TiO2-R is used as a carrier, the catalyst needs to achieve complete conversion of CO at 150°C; when octahedral TiO2-O is used as a carrier, the catalyst needs to achieve complete conversion of CO at around 180°C; and when spherical TiO2-S is used as a carrier, the catalyst can achieve complete conversion of CO at 130°C. It can be seen that the CO oxidation performance of the catalyst prepared by the present invention is closely related to the morphology of the titanium oxide carrier. Carriers with different morphologies have different specific surface areas, pore volumes and pore sizes, and these parameters affect the contact area and material transfer rate between the reactants and the catalyst, thereby affecting the catalytic reaction efficiency; and carriers with different morphologies have different surface defects, which affect the activation of O2 by surface oxygen vacancies, thereby affecting the CO oxidation performance; different carrier morphologies affect the strength of their interaction with metal species at the interface, thereby affecting the dispersion of active species and causing performance differences.
[0109] (4)Reference Figure 5 The catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention were subjected to XRD test. Figure 4 The test results show that the prepared supports of different morphologies are all anatase; and the catalysts with rod-shaped TiO2-R and octahedral TiO2-O as supports show weaker Cu XRD peaks; while the catalysts with spherical TiO2-S as supports and prepared with the same loading method and parameters do not show Cu XRD peaks, indicating that the Cu species are more dispersed and more uniform on the spherical TiO2-S supports. The spherical supports have strong interactions with the metal species at their interfaces, which can disperse and stabilize the active metal Cu, and prevent the agglomeration and growth of the metal components while promoting its high dispersion.
[0110] (5)Reference Figure 6 The catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested by electron microscope. Figure 5 From the test results, it can be seen that by comparing the electron microscope (TEM) images of the catalyst prepared in Example 1 (Figure a) of the present invention with those in Comparative Example 1 (Figure b) and Comparative Example 2 (Figure c), it is shown that the catalyst described in this patent is indeed spherical in shape, while Comparative Examples 1 and 2 are indeed rod-shaped and octahedral in shape.
[0111] (6)Reference Figure 7The Cu particle size statistics of Example 1 of the present invention and Comparative Examples 1 and 2 show that the particle size of the active component Cu in the catalyst prepared in Example 1 of the present invention is about 1.76nm; the particle size of Cu in the Cu / TiO2-R catalyst in Comparative Example 1 is about 2.06nm; the particle size of Cu in the Cu / TiO2-O catalyst in Comparative Example 2 is about 2.13nm; it can be seen that the active component Cu of the catalyst prepared by the present invention is uniformly dispersed on the titanium oxide carrier in nanometer form, and the dispersion is higher and more uniform, indicating that the CO oxidation performance of the catalyst described in this patent is closely related to the size and dispersion of the active component Cu of the catalyst. The smaller the particle size of copper in the catalyst, the more uniform the dispersion, the more effective active species, and the formation of more metal-carrier interface sites, which is conducive to the dissociation and activation of O2 and the reaction with CO to generate CO2.
[0112] (7)Reference Figure 8 , the stability of the catalysts prepared in Example 1 of the present invention and Comparative Example 2 was compared.
[0113] Depend on Figure 8 It can be seen that after 24 days of activity testing at 110°C, the CO conversion rate of Cu / TiO2-S decreased by about 4%; while the CO conversion rate of Cu / TiO2-O decreased by about 12%. It can be seen that the catalyst prepared in Example 1 of the present invention maintained a stable conversion rate in the 24-day activity test and had good stability. The catalyst stability may be related to the specific surface structure of the catalyst. In Example 1, there is a stronger interaction between the specific morphology carrier and the copper metal active component, so that the copper metal is stably and evenly dispersed on the carrier surface. In the CO catalytic oxidation stability test, the original dispersion of the copper active metal can be maintained, and the agglomeration and growth of the copper component is avoided, thereby having higher stability.
[0114] (8)Reference Fig. 9 , explore the effect of the preparation method in Example 1 of the present invention and Comparative Example 3 on the performance of the prepared catalyst.
[0115] Depend on Fig. 9It can be seen that the Cu / TiO2-S2 catalyst obtained by the same loading method using the spherical TiO2-S carrier prepared by different methods needs to achieve complete conversion of CO at about 180°C; while the catalyst described in this patent achieves complete conversion of CO at 130°C, which is much higher than the catalyst of the same morphology obtained by the same loading method using different carrier preparation methods. It can be seen that the CO oxidation activity of the catalyst prepared by the present invention is closely related to the carrier preparation method. This is because the preparation methods are different, and the nucleation rate and growth rate of the crystals are different during the preparation process, resulting in different carrier sizes and specific surface areas, which affects the performance. The carrier preparation method of the present invention obtains a carrier with moderate size and specific surface area, which is beneficial to the diffusion of reactants and products during the reaction, thereby improving the catalyst performance.
[0116] (9)Reference Fig.10 , explore the effect of the preparation method in Example 1 of the present invention and Comparative Example 4 on the performance of the prepared catalyst.
[0117] Depend on Fig.10 It can be seen that in Comparative Example 4, when commercial anatase is used as a carrier, the catalyst needs to be at 170°C to achieve complete conversion of CO; while the spherical TiO2-S prepared by the method of the embodiment of the present invention is used as a carrier, and the obtained catalyst achieves complete conversion of CO at 130°C, indicating that the performance of the catalyst prepared by the present invention using the prepared spherical TiO2-S as a carrier is better than the performance of the catalyst prepared by the same method and parameters using commercial anatase as a carrier. This is because different carrier surfaces have different atomic arrangements, which affects the interaction between the carrier and the metal active species on its surface, resulting in differences in catalytic performance. The catalyst active metal and the carrier described in Example 1 have a strong interaction force, which makes the surface copper active species more stable, not easy to form agglomerations, and has a high degree of dispersion, so the performance is good.
[0118] (10)Reference Fig.11 and Fig.12 The response of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 to CO was tested. The testing method was carried out according to the above-mentioned gas-sensitive sensing performance testing steps of the present invention to test the CO gas-sensitive sensing performance and stability of the different prepared catalysts.
[0119] Depend on Fig.11 It can be seen that at an operating voltage of 3.5V, the catalyst prepared in Example 1 and the catalysts prepared in Comparative Examples 1 and 2 all reached the best response value. The best response value of the catalyst Cu / TiO2-S prepared in Example 1 of the present invention was 19.4mV; the best response value of the catalyst Cu / TiO2-R prepared in Comparative Example 1 was 12.1mV; and the best response value of the catalyst Cu / TiO2-O prepared in Comparative Example 2 was 15.8mV. Fig.12It can be seen that the performance change range of the catalyst Cu / TiO2-S prepared in Example 1 of the present invention in the 60-day sensing stability test is smaller than that of the other two catalysts prepared in Comparative Examples 1 and 2, indicating that the sensing performance and stability of the catalyst prepared in Example 1 of the present invention are better than those of Comparative Examples 1 and 2. This is because the strong interaction between the specific morphology carrier and the copper metal active component in Example 1 makes the copper metal stably and evenly dispersed on the carrier surface, and maintains the original dispersion degree of the copper active metal in the gas-sensitive detection of CO gas, avoiding the agglomeration and growth of the copper component, so that the material has both good high response and stability. It can be seen that the catalyst Cu / TiO2-S prepared by the present invention has a response value of 19.4mV to 1000ppm CO at an operating voltage of 3.5V, and has excellent gas-sensitive sensing and monitoring sensitivity for flammable, explosive, toxic and harmful gases, and can be used for CO gas-sensitive sensors, while having CO elimination and detection functions.
[0120] (11)Reference Fig.13 , XPS test was performed on the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Fig.14 , H2-TPR test was performed on the catalysts prepared in Example 1 (Figure a) and Comparative Example 3 (Figure b) of the present invention.
[0121] Depend on Fig.13 It can be seen that the O1s XPS spectrum of the Cu / TiO2 catalyst shows three oxygen species, with binding energies at 529.6eV, 532.1eV and 534eV, respectively, which can be attributed to the lattice oxygen on the catalyst surface, the adsorbed oxygen on the oxygen vacancies and the adsorbed OH species. The adsorbed oxygen concentrations of the Cu / TiO2-S prepared in Example 1, the Cu / TiO2-R prepared in Comparative Example 2 and the Cu / TiO2-O prepared in Comparative Example 3 are calculated to be 0.69, 0.55 and 0.30, respectively, which indicates that the spherical catalyst has the most oxygen vacancies and the metal carrier interaction between the active species Cu and the spherical TiO2 is stronger.
[0122] Hydrogen-programmed temperature reduction (H2-TPR) was applied to study the surface redox properties. The reduction of cuprous oxide and cupric oxide usually occurs in a higher temperature range. When cupric oxide is supported on titania, the interaction between the copper oxide and the titania support facilitates the reduction to occur in a lower temperature range. Fig.14As shown in (a) and (b), it can be observed that the highest reduction peak of Cu / TiO2-S prepared in Example 1 is about 139°C, and most of the hydrogen consumption is below 190°C, while the highest reduction peak of the catalyst Cu / TiO2-O prepared in Comparative Example 3 is about 161°C, and most of the hydrogen consumption is below 220°C. It can be seen that the metal carrier interaction of Cu / TiO2-S prepared in Example 1 is stronger. Peaks I and II in the figure are identified as the gradual reduction of copper oxide (Cu 2+ →Cu + →Cu 0 ), peak III can be attributed to the reduction of crystalline CuO or copper species that have a strong interaction with the carrier, while the α peak is related to the highly dispersed copper species on the surface. In Figure a, the Cu / TiO2-S prepared in Example 1 has an α peak, while the catalyst Cu / TiO2-O prepared in Comparative Example 3 has no obvious manifestation, which indicates that the dispersion of copper on the Cu / TiO2-S prepared in Example 1 is higher.
[0123] In summary, the morphology of the spherical carrier can improve the dispersion of the active components on the carrier and prevent the agglomeration of the active components. In addition, the strong metal carrier effect can generate more oxygen vacancies on the catalyst surface, promote the adsorption and activation of the reactant molecules CO and O2, and improve the reaction performance.
[0124] In the description of this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0125] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0126] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0127] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A Cu / spherical anatase crystal TiO2 catalyst material, characterized in that: The catalyst material includes a TiO2 carrier and nano copper uniformly dispersed and loaded on the TiO2 carrier; The TiO2 carrier is spherical anatase crystal TiO2; The loading amount of the nano copper on the carrier is 4-6 wt %.
2. The Cu / spherical anatase crystal TiO2 catalyst material according to claim 1, characterized in that: The average particle size of the nano copper is 1.73-1.79 nm.
3. The method for preparing the catalyst material according to claim 1 or 2, characterized in that: The specific preparation process is as follows: An organic titanium precursor and anhydrous ethanol are added dropwise into an acidic aqueous solution under stirring to obtain a mixed solution, and then the mixed solution is subjected to a hydrothermal reaction; calcining the hydrothermal reaction product to obtain a spherical titanium dioxide carrier with a specific morphology; The titanium dioxide carrier is dispersed in deionized water to form a suspension, a Cu precursor solution is added thereto for deposition and precipitation, and the obtained precipitate is calcined to obtain a Cu / spherical anatase crystal TiO2 catalyst.
4. The method according to claim 3, characterized in that The hydrothermal reaction product is calcined at a temperature of 430-460° C. for 3-4 hours; and / or The precipitate is calcined at a temperature of 330-360° C. and a calcination time of 3-4 hours.
5. The method according to claim 3, characterized in that: The ratio of the organic titanium precursor to anhydrous ethanol is 1:2, and / or The organic titanium precursor is butyl titanate; and / or The acidic aqueous solution is a 1-3 mol / L sulfuric acid or hydrochloric acid solution.
6. The method according to claim 3, characterized in that The hydrothermal reaction temperature is 150-200° C., and the hydrothermal reaction time is 4-6 hours.
7. The method according to claim 3, characterized in that The metal mass concentration in the Cu precursor solution is 1.5-2 mg / mL.
8. The method according to claim 3, characterized in that The specific process of adding the Cu precursor solution to the suspension for deposition and precipitation is: adding the Cu precursor solution to the suspension, then adjusting the pH with a Na2CO3 solution, then stirring the reaction, standing for aging, filtering, washing, and drying.
9. The method according to claim 8, characterized in that The concentration of the Na2CO3 solution is 0.2 mol / L; and / or The pH value is 9 to 10; and / or The stirring reaction temperature is 80° C., the time is 3 hours, and the static aging time is 1 hour.
10. Use of the catalyst material according to claim 1 or 2 as a catalyst for catalytic oxidation of CO, characterized in that: The catalyst completely converted CO at 130°C and maintained a stable conversion rate during a 24-day activity test.
11. Using the catalyst material according to claim 1 or 2 to perform gas-sensitive monitoring of trace CO gas, characterized in that: At an operating voltage of 3.5 V, the response value of the catalyst material to 1000 ppm CO is 19.4 mV, and the catalyst material has excellent gas-sensitive sensing and monitoring sensitivity for flammable, explosive, toxic and harmful gases.